PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KUNYIT (Curcuma Longa L.) - yogi alamsyah; Adrianus Adrianus; Nurhening Y E; Mariana L Resubun (Musamus Journal of Agrotechnology Research, 2022)
ABSTRACT This research aims to determine the effect of the composition of the growing media on the growth and production of turmeric plants and to obtain the correct composition of the growing media for the growth and production of turmeric plants. This research was carried out at the screenhouse and in the laboratory of the Faculty of Agriculture, University of Musamus Merauke, from September 2021 to February 2022. This study used a non-factorial Randomized Block Design (RAK) consisting of three treatments and one control, 100 % soil, 25% soil + 75% sand, 25% soil + 75% husk, 25% soil + 75% saw dregs. The treatment was repeated six (6) times, and each replication contained three samples, and 72 experimental samples were obtained. Planting media treatment significantly affected plant height, number of tillers, number of leaves, the weight of wet stover, weight of wet rhizome rhizome, dry rhizome weight, and rhizome moisture content. The best growing media treatment for the growth and production of turmeric (Curcuma longa L.) was 25% soil + 75% husk. Keywords: turmeric, growing media, growth.